UMP introduces set of Menu Kasih Rahmah - Nor Salwana, Mohammad Idris (UMPSA, 2023)
GAMBANG, 24 February 2023 - Universiti Malaysia Pahang (UMP) launched a lunch set of Menu Kasih Rahmah offered to UMP residents that can be enjoyed at RM5.